The First Crusade the call from the East - Frankopan, Peter (Cambridge, Mass. : Belknap Press of Harvard University Press, 2012)
According to tradition, the First Crusade began at Pope Urban II{u2019}s instigation and culminated in July 1099, when western European knights liberated Jerusalem. But what if the First Crusade{u2019}s real catalyst lay far to the east of Rome? Countering nearly a millennium of scholarship, Peter Frankopan reveals the First Crusade{u2019}s untold history.
Europe in crisis -- The recovery of Constantinople -- Stability in the East -- The collapse of Asia Minor -- On the brink of disaster -- The call from the East -- The response of the west -- To the imperial city -- First encounters with the enemy -- The struggle for the soul of the crusade -- The crusade unravels -- The consequences of the First Crusade.
"First published in Great Britain in 2011 by the Bodley Head."
Includes bibliographical references and index.
Description based on print version record.
Keywords: Crusades -- First, 1096-1099.; Alexius -- I Comnenus, -- Emperor of the East, -- 1048-1118.; Byzantine Empire -- History -- Alexius I Comnenus, 1081-1118.; HISTORY / Middle East / General; Electronic books